Perception and self-perception of gender stereotypes in university students at Valparaíso region through advertising - Farías Muñoz, Lila (2018)
This research is part of the line of integration and social inclusion of the Viña del Mar University, and determines the conception that young first-year university students from the region of Valparaíso (Chile) have, about the gender stereotypes reflected in society and advertising. Advertising considers both advertising in general and that of regional uni-versities. This study is qualitative and in it, young people recognize the persistence of ma-chismo, as well as the appearance of a new feminine stereotype that demands of man a change. The models of men and women presented by the society and advertising in general are traditional. In university advertising, students recognize greater features of otherness. This view allows observing the coincidences or differences in relation to their personal vi-sion, and its incidence in the development of communication strategies.